Analisis Kemampuan Kerja Supply Chain Management pada KFC (Studi Kasus pada Aceh Fried Chicken di Deli Serdang) - Ayu Wulandari; Nurita Maha; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
This research is important to know supply chain management related to raw material inventory, especially in the food industry in small UMKM. The goal is to understand supply chain management for the procurement of raw materials. In this qualitative research method, the population and sample in the study obtained are those who are mentioned as respondents. In this qualitative research method, the sample and population in the study were found to find which one was mentioned as the respondent. Then the data collection technique in qualitative research is by interviewing. The object of this research is the respondent from SCM Aceh Fried Chicken (AFC) in Deli Serdang. This supply chain management has an effect on a very adequate supply of raw materials and good quality with excellent supply chain management will obtain a supply of raw materials and can meet the needs and demands needed at Aceh Fried Chicken in Deli Serdang. The AFC needs to continue to improve the management or governance of the UMKM supply chain so that raw materials are always sufficient and available whenever needed